The Influence of Training and Development on Employee Work Productivity through Competence as an Intervening Variable (Study of Bank BNI Employees at RM Level DKI Jakarta) - Purwantiningsih, Susy; Noerman, Teuku (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to test the research model to obtain results from the influence of training and development on work productivity through the intervening medium of the competency variable. Respondent data will be used from the results of a questionnaire distributed to BNI Relationship Manager (RM) employees located in Jakarta which was conducted online using Google Drive to 113 employees. In this research, researchers carried out five hypothesis tests based on variable indicators that had been arranged using SEM PLS (partial least square) analysis and supported by the smart PLS method. This testing includes the outer model, the inner model, and hypothesis testing. Researchers hope that this research can have theoretical implications in subsequent research. The implications of this research can also be used as input for companies to design training programs that can have an impact on increasing employee competency and work productivity.